The Initiative of Sheltering Homeless Male Children During COVID 19:A Paradigm of Social Accountability of Gezira University, Sudan - Yousif El Amin, Mohamed Taha; Mohamed, Mohamed Elimam; Taha, Sami Mahjoub; Mohamed, Alaa; Mustafa, Inshirah; Abdalla, Baderldin Elsonni (مجلة الجزيرة للعلوم الصحية; مجلد 16 عدد 1 (2020), 2020)
Due to the rapid outbreak of COVID-19 pandemic and the resultant economic constrains, different social and health services in low income and low-middle income countries have witnessed a decline in the health delivery standards, and increase in the costs.   Social distancing has become the frontline defense against the corona virus spread. In the combat for this pandemic, a lack of access to adequate housing is a potential hazard for people living a homelessness for having the disease and puts the broader population at continuous  risk. The homeless children in Sudan have always been overlooked, because of the strenuous economic crises; the authorities assigned to bear this problem are exhausted not only because of devaluation of Sudanese currency  but also the inherited wrecked system of all social welfare program. In this context, the University of Gezira addressed the housing needs of homeless children on an urgent and priority basis by procurement of an emergency accommodations for the homeless children to ensure the practicality of  physical distancing, self-isolation, quarantine and other health recommendations issued by the World Health Organization including water/sanitation, food, social and psychological supports, health services and testing for COVID-19 (according to the national policy). By doing such good initiative we can ensure their equal protection against the virus and the protection of the broader population. The result was 100% of the homeless children accommodated by the University of Gezira with no clinical suspicion for COVID-19 throughout the first three months pandemic period. The partnership in health delivery during health crises would rather provide more opportunity for optimal management of this crises.